Analisis Pengaruh Budaya Organisasi dan Motivasi Terhadap Kinerja Pegawai: Pada Balai Pengembangan Kegiatan Belajar (BPKB) Dinas Pendidikan, Pemuda dan Olahraga Provinsi Papua - Pasaribu, Lisbeth Vrike; Risamasu, Ferdinand; Arfusau, Wilhelmina A. I.; Wakarmamu, Christine M (Adhigana Papua: Jurnal Ilmiah Magister Manajemen, 2023)
The study aims to (1) determine the effect of simultaneous significant level of organizational culture, motivation for Employee Performance BPKB Papua. (2) To know abaut which variables that have a dominant influence among variables level of organizational culture, employee motivation to Performance BPKB Papua Provice.The research method using sampling survey with random sampling technique using 32 employees BPKB Papua Province. Analysis of the data used by using multiple regression statistics. The hypothesis is (1) The suspect there is a significant effect simultaneously between the culture of the organizational, the motivation for Employee Performance BPKB Papua Province. (2) Allegedly level of organizational culture has a dominant effect compared with the motivation, the Employee Performance BPKB Papua Province.The results showed that: (1) the independent variables include organizational culture, motivation, have significant impact to the Employee Performance BPKB Papua Province. It is evident from the magnitude of the coefficient of determination (R2) of 0.667 means that the contribution of organizational culture, motivation for Employee Performance BPKB Papua Province of 0.667 % and the remaining 32,3 % is influenced by other variables outsite the model study. And Strengthened by the results obtained by ANOVA test count F-30.451>F table is 2.53 then the first hypothesis is accepted (2) In partial variable organization culture has the most dominant influence test results t count 4.432 and partial regression coefficient of 0.717 (71.7 %), for the variable t = 2.577 and partial regression coefficient of 0.353 (35.3%) so that the second hiotesis unsubstantiated.